1992
DOI: 10.1002/kin.550241002
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the nitrate radical with a series of reduced organic sulphur compounds in air

Abstract: A 480 L evacuable reaction chamber, equipped with FT-IR spectroscopy on-line and ion chromatography off-line, has been used to study the gas phase reaction between the nitrate radical, NOa, and the reduced organic sulphur compounds CH~CHZSH, ( C H~C H~Z S , (CH~CHZ)ZSZ, and CH&H2SCH3 in air. The products CHaCHZS03H, SOZ, HzS04, CH3CH0, and CH~CHZONOZ were identified and quantified in the reactions of the first three compounds, CH~CHZSH, (CH3CH2),S, and (CH~CHZ)&. The reaction products were CH&HZS03H, CHaSOaH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several authors have reported the reactions of aliphatic thiols with OH 7,8 and NO 3 . 2,9 For the reactions with OH, the obtained values for the rate constants of CH 3 CH 2 SH, CH 3 CH 2 CH 2 SH and (CH 3 ) 2 CHSH at 298 K are 8 4.5 Â 10 À11 , 5.3 Â 10 À11 and 3.9 Â 10 À11 cm 3molecule À1 s À1 , respectively. Both studies 7,8 were carried out under high pressure conditions (30-100 Torr and 1 atm, respectively) and the authors conclude that the dominant reaction pathway is addition to the sulfur atom.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several authors have reported the reactions of aliphatic thiols with OH 7,8 and NO 3 . 2,9 For the reactions with OH, the obtained values for the rate constants of CH 3 CH 2 SH, CH 3 CH 2 CH 2 SH and (CH 3 ) 2 CHSH at 298 K are 8 4.5 Â 10 À11 , 5.3 Â 10 À11 and 3.9 Â 10 À11 cm 3molecule À1 s À1 , respectively. Both studies 7,8 were carried out under high pressure conditions (30-100 Torr and 1 atm, respectively) and the authors conclude that the dominant reaction pathway is addition to the sulfur atom.…”
Section: Introductionmentioning
confidence: 98%
“…Natural emissions account for about 25% of total sulfur emission 1 and reduced organic sulfur compounds have been estimated to account for approximately 25% of the total global gaseous sulfur budget. 2 These reduced organic sulfur compounds are mainly emitted from the sea surface and by biological activity. A number of these compounds have been detected in the atmosphere including COS, CS 2 , H 2 S, CH 3 SH and CH 3 SCH 3 (DMS).…”
Section: Introductionmentioning
confidence: 99%
“…Among the long-life species produced by the atmospheric air discharge, only the nitrate radical NO 3 can react with mercaptans. The kinetic constants of the secondorder reactions between NO 3 and ethyl-mercaptan C 2 H 5 -SH and methyl-mercaptan CH 3 -SH are respectively 1.2×10 -12 [10] and 9.2×10 -13 [11] cm 3 .molecule -1 .s -1 at 298 K and the reaction mechanism involves hydrogen abstraction from the -SH bond by the nitrate radical with formation of a radical R-S° and nitric acid HNO 3 [12]:…”
Section: Discussionmentioning
confidence: 99%
“…The radical R-S° can then undergo multiple reactions due to reactions with molecular oxygen and/or nitrogen oxides. Basing on the mechanism proposed by Jensen et al [12], the scheme presented in figure 6 can be suggested for the destruction of mercaptans: Figure 6. Possible mechanisms for the oxidation of C 4 H 9 SH initiated by NO 3…”
Section: Discussionmentioning
confidence: 99%